Pengaruh Profitabilitas, Nilai Perusahaan, dan Struktur Modal Terhadap Harga Saham Subsektor Kabel di Bei Periode 2020-2025 - Azhar Fikri Andhika; Diah Yudhawati; Imam Sundarta (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to examine the effect of Profitability proxied by Earnings Per Share (EPS), Firm Value proxied by Price to Book Value (PBV), and Capital Structure proxied by Debt Equity Ratio (DER) on stock prices, both partially and simultaneously.This research employs quantitative data, utilizing secondary data sources derived from the companies' financial statements The population in this study comprises 7 cable sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling process was conducted using a purposive sampling technique based on specific predetermined criteria. Through this sampling method, 6 eligible companies were selected for analysis with a six-year observation period, from 2020 to 2025. The entire data processing was analyzed utilizing EViews 13 statistical software. This study applies inferential analysis with a panel data regression method. Once the data was verified to fulfill the classical assumption tests, the Random Effect Model (REM) was determined as the most efficient and relevant model to use. Based on the hypothesis testing results, it is proven that all independent variables exert a significant influence on stock price movements, both partially and simultaneously